Eficiencia del yeso, cal, materia organica y roturación como mejoradores de la estructura de un suelo bananero - Maldonado Ereyes, Ronald Manuel (2012)
For this research the effect of calcium and organic matter, act as flocculants and cementantes of the same effect that thus helps to improve the physical condition of the soil was taken as a principle. This research was done at the hacienda Frut Victoria, owned by Eng. Carlos Borja, the reason which prompted this work was the challenge facing today that finance banana in much of its area, which is the loss of the structure of the soil, or compaction of the soil. The objectives were: test the efficiency of gypsum, carbonate of calcium, organic matter and clearing as the structure of a banana soil improvers, and determine the efficiency of these editors alone and combined on the treated soil type, for which applied the following treatments: lime (CaCO3): 1.1 and 2.2 t / ha, gypsum (CaSO4): 1.5 and 3.0 t / has, and organic matter (MO): 4.0 and 8.0 t / ha, these amendments are those applied at two levels each, in the case of lime and plaster determine the amount to apply in each product by calculating be equal in every amount applied calcium content. In addition to processing I combine them between them, and even their combinations with the highest levels became them to combine with the work of the plowing of the soil to try to get best results. The variables analyzed immunity, bulk density, total porosity, the type or form of aggregates, and the class of the structural soil aggregates, or variables that are related only to the physical condition of the soil. And generally almost all treatments in the sampling performed at nine months, bulk density returned to their initial ratings and they even exceeded in some cases the witness, so it was concluded that all the treatments had an effect on the ground but lime was who had a greater effect. And that the treatments without combination showed a better effect than the combined treatments.